Orienting Attention Within Visual Short-Term Memory: Development and Mechanisms - Shimi, A; Nobre, A; Astle, D; Scerif, G (Blackwell Publishing Inc., 2014)
How does developing attentional control operate within visual short-term memory (VSTM)? Seven-year-olds, 11-year-olds, and adults (total n = 205) were asked to report whether probe items were part of preceding visual arrays. In Experiment 1, central or peripheral cues oriented attention to the location of to-be-probed items either prior to encoding or during maintenance. Cues improved memory regardless of their position, but younger children benefited less from cues presented during maintenance, and these benefits related to VSTM span over and above basic memory in uncued trials. In Experiment 2, cues of low validity eliminated benefits, suggesting that even the youngest children use cues voluntarily, rather than automatically. These findings elucidate the close coupling between developing visuospatial attentional control and VSTM. © 2013 Society for Research in Child Development, Inc.